1983
DOI: 10.1111/j.1365-2222.1983.tb02560.x
|View full text |Cite
|
Sign up to set email alerts
|

Latent anaphylactic sensitivity of infants to cow's milk proteins

Abstract: Summary Approximately 25% of infants tested released >9% of their blood basophil histamine content in the presence of cow's milk proteins, indicating a degree or level of latent anaphylactic sensitivity to these allergens. Approximately 10% of infants show a considerably higher level of sensitivity (14‐63% histamine release). These findings fulfil an essential tenet of the modified anaphylactic hypothesis for cot‐death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…The discrepancy between our results and those described by May [I 3] may be partly explained by differences in the techniques used for histamine release but also because the earlier study [1] was of children with stich severe asthma that they had been admitted to hospital, suggesting that patient selection may have played a part. The most striking finding was the relatively poor response of leucocytes from patients who were clearly allergic to egg by several criteria; a finding similar to reports published on other types of food allergy [4][5][6][7]. When Dockhorn [7] compared the amount of histamine released in response to inhalant and food antigens using leucocytes taken from patients who had multiple allergies he found that HR to inhalant antigens was consistently higher (38-58",,) than HR to foods (11-21",,).…”
Section: Discussionsupporting
confidence: 83%
“…The discrepancy between our results and those described by May [I 3] may be partly explained by differences in the techniques used for histamine release but also because the earlier study [1] was of children with stich severe asthma that they had been admitted to hospital, suggesting that patient selection may have played a part. The most striking finding was the relatively poor response of leucocytes from patients who were clearly allergic to egg by several criteria; a finding similar to reports published on other types of food allergy [4][5][6][7]. When Dockhorn [7] compared the amount of histamine released in response to inhalant and food antigens using leucocytes taken from patients who had multiple allergies he found that HR to inhalant antigens was consistently higher (38-58",,) than HR to foods (11-21",,).…”
Section: Discussionsupporting
confidence: 83%
“…Our results are comparable with those of McLaughlan and Coombs, however, who reported that only 17% of the group showed no response to IgE antibody. 7 Our results suggest that latent sensitivity to respiratory syncytial virus antigen(s) occurs during the course of infection with respiratory syncytial virus (tables 3 and 5). Both the within group and between group comparisons suggest that challenge with respiratory syncytial virus antigen has a significant effect on release of histamine from whole blood.…”
Section: Latent Sensitisationmentioning
confidence: 60%
“…Latent anaphylactic sensitivity of infants to allergens has been shown experimentally by assay of histamine release from blood on exposure to specific allergens-for example cows' milk proteins. 7 The main aim of the present study was to find out whether latent sensitivity to respiratory Challenge reagents Goat antihuman IgE (E chain specific) was obtained from Sigma Chemicals (minimum titre 1:8).…”
Section: Introductionmentioning
confidence: 99%
“…The concept that SIDS might be due to overwhelming IgE‐mediated anaphylaxis has received some consideration. As 25% of normal infants are reputed to release large amounts of histamine from their basophils in response to milk proteins, the hypothesis that milk aspiration into the lung might trigger fatal anaphylaxis through sensitised mast cells or basophils has been proposed [6]. A study by Mirchandani et al [7] found normal serum levels of both total IgE and IgE specific for house dust mite, mould and milk protein in post‐mortem blood from SIDS subjects.…”
Section: Anaphylaxismentioning
confidence: 99%